2017
DOI: 10.1039/c7ta04074a
|View full text |Cite
|
Sign up to set email alerts
|

A general route to the synthesis of layer-by-layer structured metal organic framework/graphene oxide hybrid films for high-performance supercapacitor electrodes

Abstract: A promising strategy is demonstrated for the syntheses of metal organic framework/graphene oxide hybrid films with highly ordered layer-by-layer architecture, and the derived hybrids exhibit remarkable energy storage performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…The peak tail, which appears as a consequence of an undesirable oxygen evolution reaction-induced peak in the CV profiles when the voltage is broadened to 1.5 V or higher, indicates that the maximum working voltage of the ASC should be around 1.2 V. Such a phenomenon was explained in a similar way in the previous literatures [52,53,54]. For example, Xu et al reported that the optimized operating voltage range of the ZIF-LDH/GO//ZIF-C/G device was 0–1.6 V in order to avoid the oxygen evolution reaction at 1.6–1.8 V [55]. Elshahawy et al reported that 1.6 V was utilized to be the upper limit of the operating voltage since, when the voltage went above 1.7 V, the oxygen evolution started [56].…”
Section: Resultssupporting
confidence: 55%
“…The peak tail, which appears as a consequence of an undesirable oxygen evolution reaction-induced peak in the CV profiles when the voltage is broadened to 1.5 V or higher, indicates that the maximum working voltage of the ASC should be around 1.2 V. Such a phenomenon was explained in a similar way in the previous literatures [52,53,54]. For example, Xu et al reported that the optimized operating voltage range of the ZIF-LDH/GO//ZIF-C/G device was 0–1.6 V in order to avoid the oxygen evolution reaction at 1.6–1.8 V [55]. Elshahawy et al reported that 1.6 V was utilized to be the upper limit of the operating voltage since, when the voltage went above 1.7 V, the oxygen evolution started [56].…”
Section: Resultssupporting
confidence: 55%
“…4 For instance, Yu and co-workers have synthesised layer-by-layer structured metal organic framework/graphene oxide hybrid lms via a facile route. 5 Supercapacitors based on this hybrid exhibit high energy and power densities. In addition, a graphene/carbon nanotube (CNT)/Co 3 O 4 ternary composite has been synthesised by Zhao et al 6 The ternary composite based supercapacitor exhibits a specic capacitance of 77 F g À1 at a scan rate of 500 mV s À1 .…”
Section: Introductionmentioning
confidence: 99%
“…The transformation of these MOF-5-derived structures actually results from a diffusion-controlled exchange process 28 . In terms of our previous studies, Hmim solution could induce a weakly acidic environment (Hmim ⇌ (1-x)H + + (1-x)mim − + xHmim), which breaks ionic bonds such as Co-OH and Zn-OH 32,33 . Accordingly, one can reason that the weaker Zn-O tetrahedral coordination of MOF-5 would be deteriorated once exposed to such an environment, and Zn 2+ nodes are in an unsaturated state (Step I in Fig.…”
Section: Continuous Exchangementioning
confidence: 80%